PROYEK RENOVASI GEDUNG NEUCENTRIX KEBALEN SURABAYA - Susi Risma Aprilia (Jurnal Vokasi Teknik Sipil, 2024)
Internship practice is a program designed to provide practical work experience to students or individuals who are required to be students. The main objectives of internship practice are to develop professional skills, understand the dynamics of the workplace, apply theories that have been learned, and open up employment opportunities. The purpose of this research is to increase insight into the process of building renovation in construction projects. This research uses a literature study research method, with data collection in the form of literature reviews from journals and scientific articles. The results showed that in the construction of the renovation of the Neucentrix Kebalen data center office building, the control and monitoring process was very good and complete. All control and monitoring activities were held regularly every day, week, and month. The overall implementation of the work did not experience any obstacles thanks to the time acceleration that was implemented. However, the application of Occupational Safety & Health (OHS) at the project site is still relatively lacking, because there are still many workers who are less compliant with the application of OHS and the use of Personal Protective Equipment (PPE).